Cloning and Characterization of Immunological Properties of Haemophilus influenzae Enolase - Yesenia Osorio-Aguilar; Maria Cristina Gonzalez-Vazquez; Patricia Lozano-Zarain; Ygnacio Martinez-Laguna; Alejandro Carabarin-Lima; Rosa del Carmen Rocha-Gracia (Journal of Immunology Research)
Haemophilus influenzae is a common organism of the human upper respiratory tract; this bacterium is responsible of a wide spectrum for respiratory infections and can generate invasive diseases such as meningitis and septicemia. These infections are associated with H. influenzae encapsulated serotype b. However, the incidence of invasive disease caused by nontypeable H. influenzae (NTHi) has increased in the post-H. influenzae serotype b (Hib) vaccine era. Currently, an effective vaccine against NTHi is not available; due to this, it is important to find an antigen capable to confer protection against NTHi infection. In this study, 10 linear B cell epitopes and 13 CTL epitopes and a putative plasminogen-binding motif (252FYNKENGMY260) and the presence of enolase on the surface of different strains of H. influenzae were identified in the enolase sequence of H. influenzae. Both in silico and experimental results showed that recombinant enolase from H. influenzae is immunogenic that could induce a humoral immune response; this was observed mediating the generation of specific polyclonal antibodies anti-rNTHiENO that recognize typeable and nontypeable H. influenzae strains. The immunogenic properties and the superficial localization of enolase in H. influenzae, important characteristics to be considered as a new candidate for the development of a vaccine, were demonstrated.